2017
DOI: 10.1093/jac/dkx370
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting successful dissemination of resistance to oxazolidinones in MDR Staphylococcus epidermidis clinical isolates in a tertiary care hospital in France

Abstract: ObjectivesPatient- and procedure-related changes in modern medicine have turned CoNS into one of the major nosocomial pathogens. Treatments of CoNS infections are challenging owing to the large proportion of MDR strains and oxazolidinones often remain the last active antimicrobial molecules. Here, we have investigated a long-lasting outbreak (2010–13) due to methicillin- and linezolid-resistant (LR) CoNS (n = 168), involving 72 carriers and 49 infected patients.MethodsAntimicrobial susceptibilities were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 52 publications
2
49
0
Order By: Relevance
“…However, a short course does not seem to be associated with an increased risk of adverse renal outcomes [34]. A shorter probabilistic treatment may also be beneficial in the case of linezolid use, as it limits the development of drug resistance and reduces side-effects, which are associated with the treatment duration [7,8,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…However, a short course does not seem to be associated with an increased risk of adverse renal outcomes [34]. A shorter probabilistic treatment may also be beneficial in the case of linezolid use, as it limits the development of drug resistance and reduces side-effects, which are associated with the treatment duration [7,8,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…1 The resistant phenotype has been related to the occurrence of mutations in genes coding for the V domain of 23SrRNA and ribosomal proteins L3/L4 or cfr acquisition. 1 The LRSE-ST22 isolates have been associated with infection and colonization cases in Spain, France, Germany, and, particularly, Greece, and most of these LRSE-ST22 arise after treatment with linezolid.…”
Section: Dissemination Of Staphylococcus Epidermidis St22 With Stablementioning
confidence: 99%
“…1 The resistant phenotype has been related to the occurrence of mutations in genes coding for the V domain of 23SrRNA and ribosomal proteins L3/L4 or cfr acquisition. 1 The LRSE-ST22 isolates have been associated with infection and colonization cases in Spain, France, Germany, and, particularly, Greece, and most of these LRSE-ST22 arise after treatment with linezolid. [1][2][3][4][5][6][7] In this study, we aimed to characterize the first methicillin-and linezolid-resistant S. epidermidis from a patient without previous linezolid exposure in Turkey and to assess its genetic similarity to the close geographical S. epidermidis from Greece.…”
Section: Dissemination Of Staphylococcus Epidermidis St22 With Stablementioning
confidence: 99%
“…Furthermore, our group has recently identified that linezolid resistance in our institution is almost exclusively due to clonal spread of CC5 isolates harboring cfr and mutations in the L3 and L4 ribosomal proteins, with selection of linezolid resistance being largely attributable to prior linezolid exposure [ 12 ]. Other groups worldwide have also reported the emergence and clonal spread of CC5 isolates in settings where linezolid is commonly used [ 8 , 10 , 22 , 23 ]. In light of these data, both infection control and antimicrobial stewardship appear to play an important role in limiting the further spread of LRSE.…”
Section: Discussionmentioning
confidence: 99%